Epidendrum alieniferum - Karremans Lok, Adam Philip (2013)
The authors presents 77 species new to science, distributed from Mexico, through Central and South America, as far as Argentina. They are distributed in Colombia (33), Peru (27), Ecuador (15), Costa Rica (5), Brazil (3), French Guiana (2), and one each from Argentina, Bolivia, Mexico, Panama, Paraguay, Surinam, and Venezuela. These numbers do not add up because some species are reported from more than one country. In tackling the Paniculatum sub-group, the authors also took on the Brazilian species which have often been confused with that species, but represent a different group, the Densiflorum Group. A new sub-group within the Pseudepidendrum Group is established: the new Pluriracemosum sub-group, which though similar to the Paniculatum sub-group, is recognized by the fact that it produces new racemes from the old inflorescence. Finally, Epidendrum hemihenomenum Hágsater & Dodson is illustrated from new material from Peru.